Structural and Functional Substitution of Deleted Primary Sensory Neurons by New Growth from Intrinsic Spinal Cord Nerve Cells: An Alternative Concept in Reconstruction of Spinal Cord Circuits - James, Nicholas D.; Angéria, Maria; Bradbury, Elizabeth J.; Damberg, Peter; McMahon, Stephen B.; Risling, Mårten; Carlstedt, Thomas (Frontiers in Neurology, 2017)
In a recent clinical report, return of the tendon stretch reflex was demonstrated after spinal cord surgery in a case of total traumatic brachial plexus avulsion injury. Peripheral nerve grafts had been implanted into the spinal cord to reconnect to the peripheral nerves for motor as well as sensory function. The dorsal root ganglia (DRG) containing the primary sensory nerve cells had been surgically removed in order for secondary or spinal cord sensory neurons to extend into the periphery and replace the deleted DRG neurons. The present experimental study uses a rat injury model firstly to corroborate the clinical finding of a re-established spinal reflex arch, and secondly, to elucidate some of the potential mechanisms underlying these findings by means of morphological, immunohistochemical, and electrophysiological assessments. Our findings indicate that, after spinal cord surgery, the CNS sensory system could replace the traumatically detached original peripheral sensory connections through new neurite growth from dendrites.